Bicuspid aortic valve disease - Lee, James; Otto, Catherine (SA Heart Journal, 2017)
The prevalence of bicuspid aortic valve (BAV) disease is 0.5 - 2% of the population with a 3:1 male predominance. The genetic basis remains unknown although 9% of families have more than one affected individual. Life expectancy in patients with BAV is similar to the general population with a 10-year survival of over 95%. Adverse outcomes are most often due to aortic stenosis late in life, aortic regurgitation in young adulthood or endocarditis in a small number of patients. The BAV syndrome is also associated with an aortopathy characterised by aortic dilation and an increased risk of aortic dissection. Clinical management of patients with a BAV focuses on periodic evaluation of valve function and aortic size, patient education about the expected disease course, prevention of endocarditis and optimal timing of aortic valve replacement for stenosis and/or regurgitation; with concurrent root replacement if aortic dilation (>4.5cm diameter) is present. In addition, aortic root replacement is recommended if aortic diameter exceeds 5.5cm, even if aortic valve function remains normal.